Shopper Marketing: A Literature Review - Silveira, Paulo Duarte; Marreiros, Cristina (International Review of Management and Marketing, 2014)
Shopper marketing is a recent concept and it has been gaining importance and attention among managers and researchers. Due to its youth and increasing relevance, the purpose of this paper is to analyze, categorize, compile and analyze the existing knowledge concerning shopper marketing. The main finding of this paper is that the literature on shopper marketing is complementary and coherent, and also raises several research and managerial challenges. Besides that, there is a structural common trace on the literature, recognizing that shoppers are citizens with specific needs beyond consumption, which should be effectively analyzed and satisfied, adopting a shopper marketing approach. The main contributions provided are the compilation of shopper marketing literature, its analysis and the identification of major issues and directions for future research. Keywords: shopper marketing; in-store marketing; literature review JEL Classifications: M30; M31